(untitled) (Discourse of Law and Administration, 2026)
The publication concerns non-payment of maintenance as one of the grounds for unworthiness to inherit. The very notion of unworthiness to inherit is an important institution of inheritance law. In the Polish legal system, it was amended by the Act of 28 July 2023 amending the Civil Code and certain other acts. By virtue of the indicated legal act, the grounds for unworthiness to inherit were extended to include, among others, non-payment of alimony. The analysis of this premise of unworthiness to inherit will be based primarily on the existing literature.